Queuing System of a Busy Restaurant Using Simulation Software - Haron, Nur Arfa Aleyssa; Kamardan, Muhamad Ghazali (Enhanced Knowledge in Sciences and Technology, 2021)
Waiting times and queuing in a long line is a common phenomenon and has become a major problem in a busy restaurant. Time spent for the customers to being serve especially when waits for a long time can affect them in several of ways such as fatigue. This research is regarding a queuing simulation of a busy restaurant by using Arena Simulation Software. The purpose of this study is to explore more on Arena Simulation Software and to analyze the queuing problem at the busy restaurant. Throughout this study, there are three variables has been analyzed such as Average Waiting Time of Customer (Wq), Average Number of Waiting Customer (Lq) and Instantaneous Utilization. The result obtained from simulation for base model shows the total Average Waiting Time (Wq) of a customer in queue is 55.3131 minutes with the total Average Number of Customers Waiting in queue (Lq) is 10 and the Instantaneous Utilization of the waiters are 72.22% and 71.33% for the cashier which is consider as well utilized and in a busy condition. Therefore, the customers flow in the busy restaurant system is still needed to be improved. Based on this situation, this research also provides two (2) scenarios that help to reduce the waiting time in a busy restaurant as well as to improve the customer’s satisfaction and increase the restaurant efficiency.